The development of control system via Brain Computer Interface (BCI) - Functional Electrical Stimulation (FES) for paraplegic subject - A. Rahman, K. A.; B. S. K. K., Ibrahim; A. Jamil, M. M.; Leman, A. M. (Penerbit UTHM, 2012)
Brain is known to be one of the powerful systems in human body because of its ability to give command and communicate throughout the body. The spinal cord is the pathway for impulses from the brain to the body as well as from the body to the brain. However, the bounty of this pathway could be lost due to spinal cord injury (SCI) and that results in a loss of function especially mobility. A combination of Brain Computer Interface (BCI) and Functional Electrical Stimulation (FES) is among one of the technique to regain the mobility function of human body which will be the focused area of this research. In this study, Electroencephalography (EEG) system will be used to capture the brain signal which will then drive the FES. A paraplegic subject will be involved in this study. The subject will be required to move the knee joint with involvement few muscle contraction. Overall, in this paper the combination of BCI-FES methods for development of rehabilitation system will be proposed. From this preliminary study, it can be summarized that the combination between BCI and FES potentially would provide a better rehabilitation system for SCI patient in comparison to the conventional FES system.